Chean ki shehzadi - Iqbal kardad (Ferozsons (Pvt) Limited ; Pakistan, 2010)
"Cheen Ki Shehzadi" is an enchanting tale of courage, wisdom, and cultural heritage, centered on a Chinese princess who navigates challenges with grace and determination.